Optimal control of mutual impact of electric grids for the reduction of their electric energy losses - Lezhniuk, Petro; Rubanenko, Olexandr; Kylymchuk, Anton (Eastern-European Journal of Enterprise Technologies, 2014)
The subject of the research comprise the methods, aimed at determination of additional losses of active power, caused by forced displacement of transit transfers from high voltage (HV) into low voltage (LV) grids, which contain besides the transformers with tap-changing under load, also cross-transformers (CT). The research for the first time performs the analysis of the impact of CT location and its angle on the losses of active power in the branches of LV grid and on general system losses, that takes into consideration the change of additional losses of active power at the expense of forced displacement of transit transfers from LV grids into HV grids and vice versa. The paper contains the algorithms and explanation of their operation, that enables to determine optimal branch and CT angle, as well as, in case of their implementation, allow to decrease power losses. Results of research, considered in the paper are used in power industry, namely for calculation of normal modes and optimal parameters of control impacts vectors in order to degrease active power losses in electric grids. The results obtained in the process of the research prove that application of CT with optimal phase angle in the branch, defined by the suggested method of CT determination of CT optimal place location allows to decrease, both losses of active power in LV grids and general system losses, the degree of mutual and transit power transfers impact on the level of active electric energy losses changes depending on autotransformers transformation ratios, value of CT phase-shifting angle, circuit parameters and electric grid loading mode; studies of additional losses of active power change, caused by the displacement of transit transfers of power from HV grids into LV grids shows that sometimes: uncoordinated usage of regulating devices of the transformers in HV and LV grids leads to growth of these additional power losses; usage of transformers tap-changing under load does not allow to decrease maximally losses of active power, greater decrease of these losses can be achieved by optimal usage of СT.